Developing a historically based “Famine Vulnerability Analysis Model” (FVAM) – An interdisciplinary approach - Engler, Steven (ERDKUNDE, 2012)
This paper seeks to enhance the methodological and empirical basis of famine data analysis. It will focus on developing a new holistic, network model of famine analysis based on an understanding of vulnerability. This “Famine Vulnerability Analysis Model” will be derived from the study of historical famines of the 14th through the 21st centuries, primarily famines of the Little Ice Age. The model will help to answer questions on what drives famines, the direct impacts they have on affected groups or societies, how these cope and adapt. Using this modern vulnerability concept to analyse historical famines unpacks societal experience of the past for today’s regions at risk of famine worldwide and so can foster learning processes.